Implementation of Masbuk Hadith in Congregational Prayer: Perspectives of Today's Society - Sakka, Abdul Rahman; Rasyid, Muhammad Nur Akbar; Nurwahida, Nurwahida (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2023)
The debate among ulama over the applicability of the masbuk hadith in congregational prayer for individuals who are alone at the back of the saf and the significance of observing its application in Makassar City's Islamic community are the driving forces behind this research. This research design is qualitative in nature that combines literature study with field study. Literature study uses Syuhudi model analysis. Field study uses Miles model analysis. The results showed that scholars differed in assessing the quality of the Hadith about the rule of masbuk in congregational prayer because of the controversial narrators. Those who consider the narrator flawed, the Hadith is daif and cannot be practiced. Those who praise the narrator, the hadith is accepted and practiced. The implementation of the hadith in the religious practices of the Muslim community in Makassar City is still low, only 15.15%. The implementation of the masbuk rule in congregational prayers, the people of Makassar City practice two ways, namely choosing to stand alone at the back of the row or pulling someone in the front to go back to accompany him in the back row. The first way, reached 51.52%, the second way only 48.48%. الملخص خلفية هذا البحث هي إختلافات العلماء حول وقوف الرجل منفردا خلف الصف عند المسبوق في صلاة الجماعة، وكذلك أهمية النظر في تطبيق حديثه في المجتمع الإسلامي بمدينة مكسار. تعتمد الدراسة منهجية نوعية ويجمع بين الدراسة المكتبية والدراسة الميدانية. تستخدم الدراسة المكتبية تحليل نموذج شهودي. وأما الدراسة الميدانية تستخدم تحليل نموذج مايلز. وتظهر نتائج البحث اختلاف آراء العلماء في تقييم جودة الحديث في أحكام المسبوق في صلاة الجماعة بسبب إختلافهم علي الراوي هل كان عادلا أومجروحا. واستنتج الذين انتقدوا الراوي مجروحا أن الحديث ضعيف، فلا يمكن العمل به. ومن يعتبر الراوي عادلاً فيكون الحديث مقبولا معمولا. لا يزال تطبيق الحديث في الممارسات الدينية للمجتمعات الإسلامية في مدينة مكسار منخفضًا، حيث يبلغ 15.15% فقط. وأغلبهم يطبقون التعاليم الإسلامية المبنية على شروح الفقه الإسلامي دون فهم حديثه. تطبيق أحكام المسبوق في صلاة الجماعة التي يمارسها المجتمع الإسلامي في مدينة مكاسار. أولاً، اختر الوقوف بمفرده خلف الصف. ثانيا أو اجترر رجلا من الصف لمرافقته فيصلي معه. النموذج الأول أكثر عددا (51.52%) من النموذج الثاني فقط (48.48%) الكلمات المفتاحية: الحديث؛ مسبوق؛ صلاة الجماعة؛ السند Abstrak Penelitian ini dilatarbelakangi oleh kontroversi ulama terkait aturan masbuk dalam salat berjamaah bagi yang sendirian di belakang saf, serta pentingnya melihat implementasi hadis masbuk di masyarakat Islam di Kota Makassar. Desain penelitian ini bersifat kualitatif yang menggabungkan studi pustaka dengan studi lapangan. Studi pustaka menggunakan analisis model Syuhudi. Studi lapangan menggunakan analisis model Miles. Hasil penelitian menunjukkan bahwa ulama berbeda pendapat dalam menilai kualitas hadis tentang aturan masbuk dalam salat berjamaah, karena adanya perawi yang kontroversial. Mereka yang mencela perawi tersebut menyimpulkan bahwa hadisnya daif sehingga tidak bisa diamalkan. Mereka yang menilai perawinya terpuji, maka hadisnya dapat diterima dan diamalkan. Implementasi hadis dalam praktik keagamaan masyarakat Islam di Kota Makassar masih rendah, hanya 15.15%. Mayoritas mereka melaksanakan ajaran Islam berdasarkan penjelasan fikih ulama tanpa memahami hadisnya. Pelaksanaan aturan masbuk dalam salat berjamaah, masyarakat Kota Makassar mempraktikkan dua cara, yaitu memilih berdiri sendiri di belakang saf atau menepuk bahu seorang makmum di depan untuk mundur mendampinginya di belakang saf. Cara pertama lebih banyak, mencapai 51.52%, cara kedua hanya 48.48%. Kata Kunci: Hadis; Masbuk; Salat Berjamaah; Sanad